Analysis of Physiological Variations and Genetic Architecture for Photosynthetic Capacity of Japanese Soybean Germplasm - Shamim, Mohammad Jan; Kaga, Akito; Tanaka, Yu; Yamatani, Hiroshi; Shiraiwa, Tatsuhiko (Frontiers in Plant Science, 2022)
The culmination of conventional yield improving parameters has widened the margin between food demand and crop yield, leaving the potential yield productivity to be bridged by the manipulation of photosynthetic processes in plants. Efficient strategies to assess photosynthetic capacity in crops need to be developed to identify suitable targets that have the potential to improve photosynthetic efficiencies. Here, we assessed the photosynthetic capacity of the Japanese soybean mini core collection (GmJMC) using a newly developed high-throughput photosynthesis measurement system “MIC-100” to analyze physiological mechanisms and genetic architecture underpinning photosynthesis. K-means clustering of light-saturated photosynthesis (Asat) classified GmJMC accessions into four distinct clusters with Cluster2 comprised of highly photosynthesizing accessions. Genome-wide association analysis based on the variation of Asat revealed a significant association with a single nucleotide polymorphism (SNP) on chromosome 17. Among the candidate genes related to photosynthesis in the genomic region, variation in expression of a gene encoding G protein alpha subunit 1 (GPA1) showed a strong correlation (r = 0.72, p <0.01) with that of Asat. Among GmJMC accessions, GmJMC47 was characterized by the highest Asat, stomatal conductance (gs), stomatal density (SDensity), electron transfer rate (ETR), and light use efficiency of photosystem II (Fv’/Fm’) and the lowest non-photochemical quenching (NPQ(t)), indicating that GmJMC47 has greater CO2 supply and efficient light-harvesting systems. These results provide strong evidence that exploration of plant germplasm is a useful strategy to unlock the potential of resource use efficiencies for photosynthesis.